2021
DOI: 10.1063/5.0049213
|View full text |Cite
|
Sign up to set email alerts
|

SPH-FEM simulation of concrete breaking process due to impact of high-speed water jet

Abstract: The process of concrete breaking by a high-speed water jet was simulated in this study based on the coupled method of smoothed particle hydrodynamics and the finite element method. The Riedel–Hiermaier–Thoma constitutive model was adopted to describe the mechanical characteristics of the concrete material. Various impact velocities (250–800 m/s) and jet diameters (1.0–3.0 mm) were simulated to investigate the effect of incident parameters on the dynamic responses and damage behaviors of the concrete material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…While variance analysis was employed mainly to find the contribution of parameters, coupled methods were used to predict the optimal values of inputs. [15][16][17][18][19][20][21][22] Research on HAM of various ferrous and non-ferrous materials is observed from an exhaustive literature survey. However, a very limited analysis is available in the study of striation features and cut surface characteristics in the fabrication of the MMC Al6061/Al 2 O 3 /B 4 C using the HAM process.…”
Section: Article Pubsaiporg/aip/advmentioning
confidence: 99%
“…While variance analysis was employed mainly to find the contribution of parameters, coupled methods were used to predict the optimal values of inputs. [15][16][17][18][19][20][21][22] Research on HAM of various ferrous and non-ferrous materials is observed from an exhaustive literature survey. However, a very limited analysis is available in the study of striation features and cut surface characteristics in the fabrication of the MMC Al6061/Al 2 O 3 /B 4 C using the HAM process.…”
Section: Article Pubsaiporg/aip/advmentioning
confidence: 99%
“…A powerful water jet of up to 3000 bars removes parts of or the whole of the joints. Remote-controlled hydro demolition machines with a predefined area and depth of application exist to ensure precise removal of the mortar without creating excessive damage in the adjacent concrete [44][45][46][47]. A benefit of hydro demolition is that the dust from the removed mortar is contained in the water, which can be cleaned and reused repeatedly.…”
Section: Disassembly Process With Weak Mortar Jointsmentioning
confidence: 99%
“…Furthermore, for small deformations, the FEM proves to be more efficient than the SPH method, whereas the SPH method surpasses the FEM in efficiency for large deformations 28) . To compensate for these drawbacks, the FEM and SPH method are sometimes combined, depending on the specific simulations [29][30][31] . Combining these two methods allows us to utilize the strengths of both: the flexibility and adaptability of the SPH method and the precision of the FEM.…”
Section: Introductionmentioning
confidence: 99%